Ternary and quaternary Ni(Si)Ge(Sn) contact formation for highly strained Ge p- and n-MOSFETs. (31st March 2015) - Wirths, S; Troitsch, R; Mussler, G; Hartmann, J-M; Zaumseil, P; Schroeder, T; Mantl, S; Buca, D
Abstract: The formation of new ternary NiGeSn and quaternary NiSiGeSn alloys has been investigated to fabricate metallic contacts on high Sn content, potentially direct bandgap group IV semiconductors. (Si)GeSn layers were pseudomorphically grown on Ge buffered Si(001) by reduced pressure chemical vapor deposition. Ni, i.e. the metal of choice for source/drain metallization in Si nanoelectronics, is employed for the stano-(silicon)-germanidation of highly strained (Si)GeSn alloys. We show that NiGeSn on GeSn layers change phase from well-oriented Ni5 (GeSn)3 to poly-crystalline Ni1 (GeSn)1 at very low annealing temperatures. A large range of GeSn compositions with Sn concentrations up to 12 at.%, and SiGeSn ternaries with large Si and Sn compositions from 18%/3% to 4%/11% are investigated. In addition, the sheet resistance, of importance for electronic or optoelectronic device contacts, is quantified. The incorporation of Si extends the thermal stability of the resulting low resistive quaternary phase compared to their NiGeSn counterparts.